THE APPLICATION OF A SATELLITE SYSTEM FOR CRUSTAL DEFORMATION STUDIES - Prilepin M.T. (My University, 1988)
Measurements of crustal deformations provide important quantitative data for use in the study of the properties of materials and processes in the Earth's interior, and also for the purposes of delineation of active faults by which oil and gas deposits might be confined. Only the usage of satellite systems makes it possible to conduct deformometric studies over large areas and to accomplish measurements within reasonable time periods. The satellite system discussed here is based on the following concepts: pairs of satellites exchange phase information as the result of which the paired satellites emit coherent signal observed at ground sites by the interferometric method. In this process, the measured value is an increment of the difference of distances from the ground site to the two satellites.